"It's When the Trees Blossom": Explanatory Beliefs, Stigma, and Mental Illness in the Context of HIV in Botswana. (September 2019) - Becker, Timothy D.; Ho-Foster, Ari R.; Poku, Ohemaa B.; Marobela, Shathani; Mehta, Haitisha; Cao, Dai Thi Xuan; Yang, Lyla S.; Blank, Lilo I.; Dipatane, Vincent Ikageng; Moeng, Letumile Rogers; Molebatsi, Keneilwe; Eisenberg, Marlene M.; et al.
Mental illness is a common comorbidity of HIV and complicates treatment. In Botswana, stigma impedes treatment of mental illness. We examined explanatory beliefs about mental illness, stigma, and interactions between HIV and mental illness among 42 adults, from HIV clinic and community settings, via thematic analysis of interviews. Respondents endorse witchcraft as a predominant causal belief, in addition to drug abuse and effects of HIV. Respondents describe mental illness as occurring "when the trees blossom, " underscoring a conceptualization of it as seasonal, chronic, and often incurable and as worse than HIV. Consequently, people experiencing mental illness (PEMI) are stereotyped as dangerous, untrustworthy, and cognitively impaired and discriminated against in the workplace, relationships, and sexually, increasing vulnerability to HIV. Clinical services that address local beliefs and unique vulnerabilities of PEMI to HIV, integration with peer support and traditional healers, and rehabilitation may best address the syndemic by facilitating culturally consistent recovery-oriented care.